Predicting the UV–vis spectra of oxazine dyes - Fleming, Scott; Mills, Andrew; Tuttle, Tell (Beilstein Journal of Organic Chemistry, 2011)
In the current work we have investigated the ability of time-dependent density functional theory (TD-DFT) to predict the absorption spectra of a series of oxazine dyes and the effect of solvent on the accuracy of these predictions. Based on the results of this study, it is clear that for the series of oxazine dyes an accurate prediction of the excitation energy requires the inclusion of solvent. Implicit solvent included via a polarizable continuum approach was found to be sufficient in reproducing the excitation energies accurately in the majority of cases. Moreover, we found that the SMD solvent model, which is dependent on the full electron density of the solute without partitioning into partial charges, gave more reliable results for our systems relative to the conductor-like polarizable continuum model (CPCM), as implemented in Gaussian 09. In all cases the inclusion of solvent reduces the error in the predicted excitation energy to <0.3 eV and in the majority of cases to <0.1 eV.
Keywords: DFT; dyes; oxazine; TD-DFT; UV–vis